The biotechnological risk: fiction or reality? - ABLuisa Pfeiffer, María (Acta Bioethica, 2001)
Which is the price humanity must pay for technological progress? This article arises the question whether technology secures a moral progress, and asks what kind of relation has been established with science and its preeminence over science itself. Then follows the analysis of biotechnology applied to agriculture: confronting some data to the certainty of its innocuousness proclaimed both from specialized fields as well as from economical and political domains.